Protein phosphatase 1 regulatory inhibitor subunit 14C promotes triple‐negative breast cancer progression via sustaining inactive glycogen synthase kinase 3 beta. Issue 1 (28th January 2022) - Jian, Yunting; Kong, Lingzhi; Xu, Hongyi; Shi, Yawei; Huang, Xinjian; Zhong, Wenjing; Huang, Shumei; Li, Yue; Shi, Dongni; Xiao, Yunyun; Yang, Muwen; Li, Siqi; et al.
Abstract: Triple‐negative breast cancer (TNBC) is fast‐growing and highly metastatic with the poorest prognosis among the breast cancer subtypes. Inactivation of glycogen synthase kinase 3 beta (GSK3β) plays a vital role in the aggressiveness of TNBC; however, the underlying mechanism for sustained GSK3β inhibition remains largely unknown. Here, we find that protein phosphatase 1 regulatory inhibitor subunit 14C (PPP1R14C) is upregulated in TNBC and relevant to poor prognosis in patients. Overexpression of PPP1R14C facilitates cell proliferation and the aggressive phenotype of TNBC cells, whereas the depletion of PPP1R14C elicits opposite effects. Moreover, PPP1R14C is phosphorylated and activated by protein kinase C iota (PRKCI) at Thr73. p‐PPP1R14C then represses Ser/Thr protein phosphatase type 1 (PP1) to retain GSK3β phosphorylation at high levels. Furthermore, p‐PPP1R14C recruits E3 ligase, TRIM25, toward the ubiquitylation and degradation of non‐phosphorylated GSK3β. Importantly, the blockade of PPP1R14C phosphorylation inhibits xenograft tumorigenesis and lung metastasis of TNBC cells. These findings provide a novel mechanism for sustained GSK3β inactivation in TNBC and suggest that PPP1R14C might be a potential therapeutic target. Abstract : PPP1R14C is upregulated in TNBC, and promotes tumorigenesis and metastasis. PPP1R14C inhibits GSK3β by retaining its Ser9 phosphorylation and inducing its protein degradation. PPP1R14C is phosphorylated and activated by PRKCI. Inhibition of PPP1R14C phosphorylation represents a promising therapeutic strategy against TNBC